Повести. Рассказы - Чехов Антон Павлович (Бриллиантовая коллекция, 2008)
Экземпляры: ф10 (20220511) / Инвентарный номер: 63203 / Цена: 48.00 / Сис.шифр: Р1 / Авт.знак: Ч-56 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)1